Podatek bankowy – konsekwencje dla sektora bankowego w Polsce - Siudek, Tomasz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The paper concerns with a bank levy as an instrument of state regulation aimed at increasing the stability of the financial system. The analysis shows that in the case of Poland, an introduction of the bank levy at a rate of 0.39% of total assets would cause a significant rise in the tax burden on banks. According to our simulations, if the bank levy had been applied to the banks in the period 1999–2009, the total return on assets (ROA) and return on equity (ROE) would have gone down respectively by 0.39% and 5.90%. As a result, development of the banking sector, considered as a main driver of national economy, would have been slower.